Artificial Intelligence In Education: Enhancing Learning And Teaching And Achieving Sustainable Development - زرقي , عائشة; بوزريعة , ايمان (مجلة دراسات في سيكولوجية الانحراف, 2025)
Abstract The integration of artificial intelligence (AI) into education is revolutionizing teaching and Learning while addressing global challenges. AI technologies like intelligent tutoring systems and adaptive learning platforms are transforming classrooms by providing personalized instruction and real-time feedback. These advancements also play a crucial role in promoting sustainable development by improving access to quality education, optimizing resource use, and fostering inclusive learning environments. This aligns with the United Nations' Sustainable Development Goals, particularly Goal 4: Quality Education. This article explores AI's dual impact in education: enhancing learning and teaching while supporting broader sustainable development objectives. We will examine recent studies on AI implementation in educational contexts, its benefits, and the challenges that need to be addressed to fully harness its potential. By doing so, we aim to understand how AI can shape a more effective and sustainable educational landscape